PENGARUH RETURN ON EQUITY (ROE), NET PROFIT MARGIN (NPM), GROSS PROFIT MARGIN (GPM) DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM (Studi Empiris Pada Perusahaan Yang Terdaftar Dalam LQ 45 BEI Periode 2013-2016) - Putri Nur Indahsafitri; Budi Wahono; Muhammad Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTThe purpose of this research is to analyze how influence on partial testReturn On Equity (ROE), Net Profit Margin (NPM), Gross Profit Margin (GPM),and Earning Per Share (EPS) to stock price on companies listed in LQ 45 BEIperiod 2013-2016. This research includes the type of this research is quantitativeresearch used secondary data with financial report on the LQ 45 index. Thesamples are having 21 from 64 companies which listed in LQ 45 index. Techniquewhich taken with purposive sampling. Methods of data analyze used multiplelinear regressions analysis with a testing hypothesis by T test. The result of thisresearch included that Return On Equity (ROE) is not had significant influence tothe stock price and negative influence, Net Profit Margin (NPM) had significantinfluence to the stock price and negative influence, Gross Profit Margin (GPM)had significant influence to the stock price and positive influence, Earning PerShare (EPS) had significant influence to the stock price and positive influence.Keywords: Return On Equity (ROE), Net Profit Margin (NPM), Gross ProfitMargin (GPM), Earning Per Share (EPS), and Stock Price.